2021
DOI: 10.3390/s21186106
|View full text |Cite
|
Sign up to set email alerts
|

Wearable, Integrated EEG–fNIRS Technologies: A Review

Abstract: There has been considerable interest in applying electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS) simultaneously for multimodal assessment of brain function. EEG–fNIRS can provide a comprehensive picture of brain electrical and hemodynamic function and has been applied across various fields of brain science. The development of wearable, mechanically and electrically integrated EEG–fNIRS technology is a critical next step in the evolution of this field. A suitable system design cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 67 publications
(162 reference statements)
0
43
0
Order By: Relevance
“…Other modalities have been explored, e.g., functional magnetic resonance imaging (fMRI) [ 37 ], functional near-infrared spectroscopy (fNIRS) [ 38 ], magnetoencephalography (MEG) [ 39 ], and electrical impedance tomography (EIT) [ 40 ]. Due to portability, non-invasiveness, and cost-effectiveness, EEG and fNIRS have an advantage in natural environment applications [ 41 ]. In terms of classification accuracy, EEG-based BMI outperforms fNIRS-based BMI [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other modalities have been explored, e.g., functional magnetic resonance imaging (fMRI) [ 37 ], functional near-infrared spectroscopy (fNIRS) [ 38 ], magnetoencephalography (MEG) [ 39 ], and electrical impedance tomography (EIT) [ 40 ]. Due to portability, non-invasiveness, and cost-effectiveness, EEG and fNIRS have an advantage in natural environment applications [ 41 ]. In terms of classification accuracy, EEG-based BMI outperforms fNIRS-based BMI [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the machines are not reliable enough to be used for real applications. Current research is looking at dual fNIRS and EEG in data acquisition for BCI [65]. It has been reported that these hybrid systems are more accurate than EEG alone or fNIRS alone.…”
Section: Future Directionsmentioning
confidence: 99%
“…As the proposed system combines two electrically separate systems (EEG and fNIRS), electrical crosstalk between these systems may occur due to field coupling between the switching current in the fNIRS optode wires and the EEG electrodes [5,28,29]. To assess the impact of the LED switching current in EEG, a resistive network phantom with electrodes positioned according to 10-20 system positions was used following the method of a study carried out in 2017 by von Lühmann, et al [28], which specified the phantom details and the experimental conditions that should be followed to assess the crosstalk in EEG in hybrid systems.…”
Section: Electrical Crosstalk Between Eeg and Fnirs Signalsmentioning
confidence: 99%
“…The main components of fNIRS systems are sources (such as LEDs, laser diodes, and VCSELs) with a driving circuit, detectors such as photodiodes (PDs) and silicon photomultipliers (SiMP) for detecting light, amplifiers, filters to reduce noise, and a recording system to display and store the fNIRS signal. The advantages of EEG and fNIRS make them the most suitable techniques for multimodal studies [5].…”
Section: Introductionmentioning
confidence: 99%